PENGARUH RASIO LANCAR DAN PENDAPATAN PER SAHAM TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dea Novita Sari; Irawan Noor (Jurnal Ekonomi dan Industri, 2023)
This study aims to determine the effect of current ratio and earning per share on stock prices in Automotive and Component sub-sector companies listed on the Indonesia stock exchange. The sample of this study was carried out using purposive sampling method. The data analysis technique in this study is to use quantitative descriptive research methods. The method of determining the sample of this study using purpose sampling, the result current ratio and earning per share simultaneously have an influence on stock prices. Current ratio partially has an influence on stock prices. Earning per share partially has an influence on stock prices.